Assessment of the performance of some new insecticides for the control of the vine mealybug Planococcus ficus in a Tunisian vineyard - Mansour, R.; Grissa Lebdi, K.; Rezgui, S. (ENTOMOLOGIA HELLENICA, 2017)
Mealybugs (Hemiptera: Pseudococcidae) cause major economic losses in many Tunisian grapegrowing areas. In an attempt to improve management strategies for the Vine Mealybug (VM) Planococcus ficus (Signoret), three insecticides, imidacloprid, Prev-Am® and spirotetramat, were evaluated for their effect on this insect on vine, with reference to methidathion. The systemic insecticide spirotetramat (Movento® 150 OD) provided the greatest control performance of the VM populations, compared to the contact insecticide methidathion, the systemic insecticide imidacloprid applied through furrow irrigated system, and to Prev-Am®, a new contact biopesticide. Three weeks after treatment, VM eggs and adult females were missing from spirotetramat-treated vines. Additionally, spirotetramat supplied a long-residual activity against VM populations and prevented further spread of these insects on vine leaves. Therefore, this new systemic insecticide could be incorporated in an Integrated Pest Management program for VM control in Tunisian vineyards. Despite its short-residual activity, Prev-Am® was shown to be more effective than both methidathion and imidacloprid, mainly on VM eggs and L3 nymphs, and resulted in the highest level of VM L1-L2 nymph decrease on vine trunks. Hence, this biopesticide might prove useful for VM management in vineyards.